Research on Legal Regulation of Internet Platforms - Yifei Tian (Теоретическая и прикладная юриспруденция)
With the development of technology, Internet platforms continue to accumulate technological advantages and become super network platforms with rapid growth in the number of users and huge transaction scale, thus triggering problems such as platform monopoly, infringement of users’ rights and interference with social governance. When the state and the government face the challenge of platform governance, the existence of a technological divide makes it difﬁcult to achieve the desired effect of Internet platform governance through the traditional unilateral regulatory model. When the law grants power, appropriate measures should be taken at the same time to avoid the abuse of power. With fairness as the regulatory goal of Internet platforms, it is necessary to start the restraint of platform power from multiple perspectives of self-regulation, cooperative regulation and external regulation to promote the standardized operation of Internet platforms.